Peculiarities of small unmanned aerial vehicles detection and recognition - Kartashov, V.M.; Oleynikov, V.N.; Sheyko, S.A.; Babkin, S.I.; Koryttsev, I.V.; Zubkov, O.V. (Radiotekhnika, 2018)
Review and analysis of methods for detection and recognition of unmanned aerial vehicles (UAVs) are conducted. The channels for the detection of UAVs - acoustic, optical, radar, infrared, radio channel are considered. The advantages and disadvantages of the channels used are compared and appreciated. In the case of small UAVs, there are a number of significant difficulties and limitations. One of the directions in the UAVs detection  is acoustic observation. The noise generated by the UAV propulsion system and the air propeller is a significant demasking feature. Creating and improving methods for detecting, guiding and recognizing small UAVs by the reception and processing their sound signals is an urgent task. When using such a method of detecting UAVs, frequency spectra, spectrograms, normalized autocorrelation functions, and phase portraits of acoustic signals are used. Estimates of spectral coefficients, determined by a discrete realization containing a predetermined number of samples, as well as parameters of autoregression models can serve as information signs of the UAVs sound image.